MENGEMBANGKAN TEOLOGI SIBER DI INDONESIA - Sefrianus Juhani (Institut Filsafat dan Teknologi Kreatif Ledalero, 2019)
Abstract: Does the internet change the way of thinking from the people and members of the Church in Indonesia? I give a “yes” answer to this question. This answer was born from the reality that digital technology is not limited as a means or instrument that helps humans to achieve a better life. More than that, the internet has become a space of life that determines and gives meaning to human existence and the existence of the Indonesian Church. The internet also creates a culture called cyber culture. If the internet breeds new logical thinking and culture, and its existence has seized the attention of members of the Catholic Church, so the internet can become locus theologicus. The existence of the internet as a locus of theology is confirmed by the Popes.Seeing this reality, the Indonesian Catholic Church through the theologians need to develop a new theology, namely cyber theology. Through this cyber theology, the members of the Church find that the sophisticated communication technology reflects Christianism which is fundamentally a communicative event.Keywords: Cyber theology, internet, Indonesian Church, cyber culture